Lead, Cadmium, and Arsenic in Raw Cow’s Milk in a Central Andean Area and Risks for the Peruvian Populations. - Castro-Bedriñana, Jorge (2023)
Milk and its derivatives are basic foods in Peru, especially for children. The Junín region, in the central Andes, is one of the leading dairy basins. However, the safety of milk is affected by mining–metallurgical activities, wastewater dumping, organic residues, and inappropriate use of organophosphate fertilizers in agriculture whose contaminants reach the food chain, putting human health at risk. The purpose of this study was to evaluate the bioaccumulation of lead (Pb), cadmium (Cd), and arsenic (As) in milk produced on a representative farm in central Peru, which uses phosphorous agrochemicals and is adjacent to a small mineral concentrator and a municipal solid waste dump, and to evaluate the potential risk for the Peruvian population of 2–85 years considering three levels of daily intake by age, which constitutes the innovative contribution of the study. These three elements were quantified by flame atomic absorption spectrometry following standardized procedures. The mean contents of Pb (0.062 mg/kg), Cd (0.014 mg/kg), and As (0.030 mg/kg) in milk exceeded the maximum limits allowed by international standards. At all ages, the target quotient hazard followed a descending order of As > Pb > Cd, being > 1 in the case of As. The hazard index was >1 for children under 7, 9, and 11 years of age in the scenarios of low, medium, and high milk intake. The information is valid for formulating policies to prevent adverse health effects and develop standards and awareness programs, monitoring, and control of heavy metals in milk in Peru.